Low-dose N-acetyl cysteine prevents paraquat-induced mortality in Caenorhabditis ele-gans - Gonzales Moreno, Candelaria (2023)
Exposure to the herbicide paraquat (PQ; 1,1′-dimethyl-4,4′-bipyridinium dichloride) affects the redox balance of the cell, an effect that can be restored by antioxidants, including N-acetyl cysteine (NAC). One hour of exposure to PQ (0 mM, 10 mM, 50 mM, or 100 mM) dose-dependently increased mortality in Caenorhabditis elegans after exposure (immediate toxicity), while this effect was more evident 24 hours thereafter (delayed toxicity). Importantly, pretreatment with NAC 0.5 mM for one hour partially prevented mortality in the immediate assay, while it had no effect in the delayed test, revealing the importance of long-term studies when evaluating toxicity.